Occurrence of the millipede genus Piccola Attems, 1953 in China (Diplopoda: Polydesmida: Paradoxosomatidae) - Liu, Weixin; Tian, Mingyi (Zootaxa, 2015)
Piccola golovatchi sp. nov. is described and illustrated. It comes from the limestone cave called Shizikou Dadong, Tianlin County, Guangxi Zhuang Autonomous Region, southern China. This species is considered to be a troglobite, showing a pallid tegument and extremely enlongated antennae and legs. This is the first record of the millipede genus Piccola Attems, 1953 from China.